2020
DOI: 10.3390/microorganisms8040581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculum Pretreatment on the Composition of Microbial Communities in Anaerobic Digesters Producing Volatile Fatty Acids

Abstract: Volatile fatty acids (VFAs) are intermediates in the methane formation pathway of anaerobic digestion and can be produced through the fermentation of organic wastes. VFAs have become an anticipated resource- and cost-effective way to replace fossil resources with higher added value and more versatile fuels and chemicals. However, there are still challenges in the production of targeted compounds from diverse and complex biomasses, such as urban biowastes. In this study, the aim was to modulate the microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…In the second step of AD (5 th -6 th day) we observed an increase in pH value to 7.3 for BM and 6.9 for SS and diminution of VFAs to 0.8 for BM and 1.8 g/L for SS. This complies with the results obtained by Blasco et al [41]. This is explained by the value buffer of pH and the consumption of the VFAs by bacteria [42].…”
Section: Effect Of Heavy Metals Present In the Considered Inocula On Adsupporting
confidence: 93%
See 1 more Smart Citation
“…In the second step of AD (5 th -6 th day) we observed an increase in pH value to 7.3 for BM and 6.9 for SS and diminution of VFAs to 0.8 for BM and 1.8 g/L for SS. This complies with the results obtained by Blasco et al [41]. This is explained by the value buffer of pH and the consumption of the VFAs by bacteria [42].…”
Section: Effect Of Heavy Metals Present In the Considered Inocula On Adsupporting
confidence: 93%
“…The last step (5 th -6 th day) shows the stabilization of biogas production and the end of the methane, The accumulation of hydrogen develops significant pressure which blocks the activity of acetogenic bacteria that stop acetate production. Due to the symbiotic relation between acetogenic and methanogenic bacteria, these latter utilize this hydrogen in methane production and significant hydrogen pressure does not occur [38][39][40][41][42][43][44][45].…”
Section: Impact Of H2o2 Pretreatment Coupled With the Us On Biogas And Methane Productionmentioning
confidence: 99%
“…Moreover, research has indicated that B. subtilis can induce a shift toward butyrate-producing bacteria in the broiler gut microbiome ( Jacquier et al., 2019 ), which was consistent with our results. Per the outcome of LEfSe higher levels of bacteria associated with the production of SCFAs, such as the unclassified_f_Lachnospiraceae, g_Ruminococcus , and g_Faecalibacterium , amongst others ( Antonissen et al., 2016 ; Blasco et al., 2020 ), were detected after B. subtilis or B. licheniformis supplementation. Considering these combined results, it may explain the significant increase in level of the SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides are known to be major producers of branched-chain amino acids, acetic acid, and butyric acid [ 49 , 50 ]. In addition, the most abundant phyla involved in the fermentation of glucose were Firmicutes , Bacteroidetes , and Proteobacteria, of which especially Firmicutes (genus Clostridium ) were connected to the highest production of SCFAs [ 51 ]. Firmicutes are known to produce butyrate and other SCFAs to maintain intestinal health by suppressing inflammation and providing energy to enterocytes [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%